Philosophy for life/ edited by M.A.Lavery - "Read, Rupert" (London, 2007)
With the same extraordinary skill that he used to demystify scientific abstraction and the new physics, Gary Zukay, the award-winning author of The Dancing Wu Li Masters, here takes us on a brilliant and penetrating exploration of the new phase of evolution we have now entered. With lucidity and elegance, Zukav explains that we are evolving from a species that pursues power based upon the perceptions of the five senses -- external power -- into a species that pursues authentic power -- power that is based upon the perceptions and values of the spirit. He shows how the pursuit of external power has produced our survival-of-the-fittest understanding of evolution, generated conflict between lovers, communities, and superpowers, and brought us to the edge of destruction. Using his scientist's eye and philosopher's heart, Zukav shows how infusing the activities of life with reverence, compassion, and trust makes them come alive with meaning and purpose. He illustrates how the emerging values of the spirit are changing marriages into spiritual partnerships, psychology into spiritual psychology, and transforming our everyday lives. The Seat of the Soul describes the remarkable journey to the spirit that each of us is on
Keywords: Ethics